A Case of Undiagnosed Craniopharyngioma in an Army Mechanic. Issue 2 (1st February 2016) - Lee, Douglas Y.; Mathis, Derek A.
ABSTRACT: Primary care providers are often the initial evaluators of soldiers presenting with acute eye complaints. It is crucial for these providers to master performing the basic eye examination with a systematic approach. Obtaining a thorough history is an important first step to the eye examination, but providers need to be careful not to narrow the diagnosis solely based on the history. Regardless of the presentation of the ocular complaints, a complete ocular examination must be performed. This article presents a case of brain tumor in an active duty soldier who was initially undiagnosed because of its unusual presentation.